Tomatoes 2005
DOI: 10.1079/9780851993966.0145
|View full text |Cite
|
Sign up to set email alerts
|

Fruit ripening and fruit quality.

Abstract: This chapter covers the following subjects: ripeness classification of tomatoes, measurements of fruit ripeness, the respiratory and ethylene climacteric, quality characteristics (pigments, size and shape, surface appearance, firmness, composition and flavour, volatiles, vitamins, and physiological disorders), and genetic improvements (achieved by traditional breeding techniques and genetic engineering).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 0 publications
2
43
0
3
Order By: Relevance
“…In the same way, Khah et al (2006) reported nonsignificant differences in fruit firmness between grafted and nongrafted plants using 'Heman' and 'Primavera' as rootstocks and 'Big Red' as a scion. With regard to TSS content, there is no consensus on the effect of grafting on this variable; some studies have reported a negative effect on this trait (Khah et al, 2006;Turkmen et al, 2010), which may be a disadvantage for the rootstocks used in those works due to that TSS content is one of the most important characteristics for fruit flavor (Saltveit, 2005). In the present study, none of the Mexican native tomato rootstocks reduced the TSS content when 'El Cid' was used as scion, which represents an advantage over the commercial rootstocks ('Maxifort' and 'Multifort'), which had values of 3.2 and 3.1 °Brix, respectively, being a reduction of 14% and 16%, in the same order, compared to ungrafted plants.…”
Section: Resultsmentioning
confidence: 99%
“…In the same way, Khah et al (2006) reported nonsignificant differences in fruit firmness between grafted and nongrafted plants using 'Heman' and 'Primavera' as rootstocks and 'Big Red' as a scion. With regard to TSS content, there is no consensus on the effect of grafting on this variable; some studies have reported a negative effect on this trait (Khah et al, 2006;Turkmen et al, 2010), which may be a disadvantage for the rootstocks used in those works due to that TSS content is one of the most important characteristics for fruit flavor (Saltveit, 2005). In the present study, none of the Mexican native tomato rootstocks reduced the TSS content when 'El Cid' was used as scion, which represents an advantage over the commercial rootstocks ('Maxifort' and 'Multifort'), which had values of 3.2 and 3.1 °Brix, respectively, being a reduction of 14% and 16%, in the same order, compared to ungrafted plants.…”
Section: Resultsmentioning
confidence: 99%
“…Sweetness of tomato fruit was correlated not only with sucrose equivalents and pH but also with the volatiles including cis-3-hexenal, trans-2-hexenal, cis-3-hexanol, geranyl-acetone, 2-methylbutanol, 3-methylbutanol trans-2-heptenal, 6-methyl-5-hepten-2-one and 1-nitro-2-phenylethane. Likewise, sourness was correlated with soluble solids and pH along with the volatiles including acetaldehyde, acetone, 2-isobutylthiazole, geranyl-acetone, beta-ionone, hexanal and ethanol (Saltveit 2005).…”
Section: Influence Of the Internal Atmosphere On Ripening And Ripeninmentioning
confidence: 99%
“…It decomposes to ethylene, with the rate of decomposition depending on pH, temperature, concentration, and the degree of penetration of the tomato tissue (Saltveit, 2005a). When the fruits reach the breaker stage, internally synthesized ethylene sustains its own synthesis and stimulates ripening, even when the external concentration of ethylene has dropped to zero.…”
Section: Introductionmentioning
confidence: 99%